The role of magnesium in pancreatic beta-cell function and homeostasis - Akimbekov, Nuraly S.; Coban, Seval Ozkan; Atfi, Azeddine; Razzaque, Mohammed S. (Frontiers in Nutrition, 2024)
Magnesium plays an essential role in glucose utilization and insulin signaling. Recent advances have revealed a greater prevalence of hypomagnesemia in general, and low intracellular magnesium levels in individuals with diabetes contribute to β-cell dysfunction and insulin resistance. This article describes the documented effects of magnesium on various aspects of β-cells and glucose homeostasis. Studies have demonstrated that magnesium deficiency is associated with reduced pancreatic β-cell activity and increased insulin resistance in patients with type 2 diabetes. Additionally, magnesium is involved in many cellular events, including energy homeostasis, protein synthesis, and DNA stability. Furthermore, magnesium is critical for proper glucose utilization and insulin signaling, and magnesium deficiency can lead to the dysregulation of ATP-sensitive potassium (KATP) channels in pancreatic β-cells, impairing insulin secretion. Therefore, maintaining adequate magnesium levels is crucial for maintaining overall health and preventing of metabolic disorders such as type 2 diabetes.